Costimulation Blockade in Kidney Transplantation: An Update - Malvezzi, Paolo (Transplantation, 2016)
In the setting of solid-organ transplantation, calcineurin inhibitor (CNI)-based therapy remains the cornerstone of immunosuppression. However, long-term use of CNIs is associated with some degree of nephrotoxicity. This has led to exploring the blockade of some costimulation pathways as an efficient immunosuppressive tool instead of using CNIs. The only agent already in clinical use and approved by the health authorities for kidney transplant patients is belatacept (Nulojix), a fusion protein that interferes with cytotoxic T lymphocyte-associated protein 4. Belatacept has been demonstrated to be as efficient as cyclosporine-based immunosuppression and is associated with significantly better renal function, that is, no nephrotoxicity. However, in the immediate posttransplant period, significantly more mild/moderate episodes of acute rejection have been reported, favored by the fact that cytotoxic T lymphocyte-associated protein pathway has an inhibitory effect on the alloimmune response; thereby its inhibition is detrimental in this regard. This has led to the development of antibodies that target CD28. The most advanced is FR104, it has shown promise in nonhuman primate models of autoimmune diseases and allotransplantation. In addition, research into blocking the CD40-CD154 pathway is underway. A phase II study testing ASK1240, that is, anti-CD40 antibody has been completed, and the results are pending.